Kompresi Video Digital Menggunakan Metode Embedded Zerotree Wavelet (EZW) - Rosdelima Parapat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In the era of technology in the field of multimedia, especially in processing moving images or often called digital video, it is very fast and competes in image and sound quality. Video files in MP4 format are very widely used today on social media which results in little storage space remaining in memory. Data compression is a process that can convert an input data stream (original data) into another data stream (compressed data) which has a smaller size. The compression process is the process of reducing the size of a data to produce a digital representation that is dense or compact but can still represent the quantity of information contained. Digital video is a computer file that is used to store a collection of digital files such as video, audio, metadata, information, chapter divisions, and titles at once, which can be played or used through certain software on a computer. There are many data compression methods currently available, but in this study the working principle of the EZW method will be discussed. The Embedded Zerotree Wavelet (EZW) method is an image compression algorithm that is simple, very effective, has properties where the bits in the bit stream are sorted according to their importance and produces a fully embedded code